OVERSEAS CORRESPONDING APPLICATION SALES MANAGEMENT SERVER SYSTEM - TERADA AKIHIRO; NISHI KOJI (2020)
To check promptly and appropriately a customer who requests to purchase 3rd party apps developed by 3rd parties in application stores operating in foreign countries.SOLUTION: A management server 100 manages online store sales, which allows a user to purchase only applications registered for online store sales stored in the app DB 250, and comprises an order processing unit 112 determining whether the application requested to be purchased by a user is a 3rd party developed 3rd app or not, and a sales approval processing unit 113 that notifies the user that, when the application requested to be purchased is a 3rd app, the application is awaiting approval by the 3rd party and notifies the 3rd party of a customer check request to obtain approval for the sale of the 3rd app.SELECTED DRAWING: Figure 1 【課題】海外の国において運営するアプリケーションストアで、３ｒｄパーティの開発した３ｒｄアプリの購入要求に際して、顧客チェックを速やかに適切に行う。【解決手段】管理サーバ１００は、アプリＤＢ２５０に記憶されたオンラインストア販売登録されたアプリケーションのみを購入可能とするオンラインストア販売を管理し、ユーザから購入要求されたアプリケーションが３ｒｄパーティの開発した３ｒｄアプリであるか否かを判定する発注処理部１１２と、購入要求されたアプリケーションが３ｒｄアプリの場合、ユーザに対して３ｒｄパーティによる承認待ちであることを通知し、３ｒｄパーティに対して顧客チェック要求を通知することで、３ｒｄアプリの販売の承認を得る販売承認処理部１１３と、を備える。【選択図】図１